Ethanolic Extract of Ginger on the Histology of the Pancrease in Adult Wistar Rats - Obeten, Kebe E; Ede, Patrick O; Isaac, Victoria N; Obasee, Patricia P (International Journal of Medical and Health Sciences Research, 2014)
Zingerber offinale (ginger) is an underground stem or rhizome which is known to have originated from Asia and have been reported to have a number of medicinal properties which is used in the treatment of many ailments such as arthritis, painful menstrual periods, nausea etc. It is also used as a common specie in food and bakery industries. Due to the availability and medicinal uses of ginger, the effect of the ethanolic extract on the histology of the pancreas of adult wistar rats was investigated. Twenty five (25) adult Wistar rats weighing 125-200g were divided into five groups (A, B, C, D and E) each with five rats. The animals in group A and B served as control groups and received distilled water and olive oil respectively, the animals in groups C, D and E served as experimental groups, and received 100mg/kg, 250mg/kg and 500mg/kg body weight of the ethanolic extract of Zingiber officinale respectively. The animals received the extract for 14 days and were sacrificed 24 hours after the last administration and routinely processed histologically. The study shows that there is disintegration of the islet cells of Langerhans (IL) with pyknotic nuclei, but no visible change or alteration in the serous acini (SA) of the pancreas. It is observed that extract of ginger has adverse effect on the integrity of the islet cells of Langerhans.